A Review of the Combined Threats of Road Salts and Heavy Metals to Freshwater Systems. (7th March 2018) - Schuler, Matthew S; Relyea, Rick A
Abstract: Road salts are altering and mobilizing heavy metals away from roadside soils, potentially into freshwater systems. Despite numerous studies investigating the mobilization of heavy metals by road salts, few studies have investigated (a) the movement rate and fate of heavy metals mobilized by road salts, (b) how road salts alter the bioavailable fraction of heavy metals, and (c) how road salts and heavy metals interact to affect freshwater organisms or human health. In this article, we discuss the consequences of increased concentrations of heavy metals and road salts, examine the mechanisms of heavy-metal mobilization, and highlight areas for future research. Future studies should investigate how metals and road salts alter ecosystem function and ecosystem services in freshwater habitats. Finally, increased research efforts will help assess whether the fate of heavy metals mobilized by road salts increases risks to human health by contaminating drinking water and water used for agriculture.